Feelings and Religiosity Interlacing in the Face of Breast Cancer Diagnosis: A Netnographic Study (Global Journal of Medical Research, 2023)
Globally female breast cancer exceeded lung cancer as the most commonly diagnosed cancer with an estimated 2 3 million new yearly cases This pathology produces profound changes in women s lives Religiosity and spirituality are essential resources at diagnosis and when making therapeutic decisions We aimed to analyze women s feelings in the face of breast cancer diagnosis and faith as an ally in confronting the disease Netnographic research was conducted in February 2023 on the Oncoguia website from testimonials in the Patient Space section We analyzed testimonials of women diagnosed with healed or in treatment breast cancer who mentioned in writing words about faith religiosity or spirituality Two researchers read and analyzed the reports organizing them into two themes Diagnosis and explosion of feelings and Faith the greatest ally in the fight against cancer We observed that multiple feelings emerge at diagnosis including despair and uncertainties In this process faith is vital for deponents to favor the quality of life and confront breast cancer
Keywords: breast cancer; faith; spirituality; religiosity; netnographic study